Differentiating Pu‐erh raw tea from different geographical origins by 1H‐NMR and U‐HPLC/Q‐TOF‐MS combined with chemometrics. Issue 3 (18th February 2021) - Wu, Xia; Liu, Ying; Guo, Jieqing; Wang, Juanxia; Li, Meizhen; Tan, Youzhen; Zheng, Qifan; Feng, Yifan
Abstract: Pu‐erh tea is believed to be a beneficial beverage for health due to its many kinds of pharmacological effects. Nevertheless, detailed information related to differences in metabolites of Pu‐erh raw tea from different geographical origins remains scarce. In this study, 43 elements were found in water‐soluble components of Pu‐erh raw tea by highly sensitive ultra‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry (U‐HPLC/Q‐TOF‐MS). The characteristic groups of 29 metabolites from nondestructive proton nuclear magnetic resonance ( 1 H‐NMR) spectroscopy were assigned. The variables contributed largely to the origin classification, mainly including valine, threonine, chlorogenic acid, quinic acid, epiafzelechin, and gallic acid ester, were screened out by sparse partial least squares discriminant analysis (sPLS‐DA) method. This study provided a feasible and rapid technique for distinguishing Pu‐erh tea from different areas by 1 H‐NMR combined with sPLS‐DA.